Model Deteksi Krisis Indonesia dengan Indikator Suku Bunga Simpanan Riil - Rina Safitri; Sugiyanto Sugiyanto; Sri Sulistijowati Handajani (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
The financial crisis is a condition where a country's finances experience a disruption which is characterized by a drastic increase in the inflation rate, a weakening currency exchange rate, and a decrease in other economic activities. Indonesia experienced financial crises in 1997 and 1998 which resulted in a collapse of financial conditions and national stability. Therefore, it is necessary to have a model to find out the crisis, so that efforts to recover the impact of the crisis can be done as early as possible from the model. This study aims to apply the Markov Switching Error Correction Model to detect a crisis. Based on the indicator of real deposit interest rates it can be concluded that the MS-ECM can explain the crisis that occurred in mid-1997 and late 2005